Descartes’ influence on Chomsky’s theory and his analysis of language - Salaah Rashid, Huda (Opción, 2019)
The world thinker, Noam Chomsky, is one of the most prominent thinkers in the field of language, politics and culture in general, for his knowledge of these fields. His ideas have revolutionized, especially in the field of langua- ge and the modern outlook on linguistic sciences. These ideas formed an important turning point in this cognitive field which has been demonstrated by the inability of the experimental behavioral model to explain the language. Chomsky’s revolution on behaviorists is an independent stage in the history of linguistics. It is a critical view that can only be understood if we address the rational origins from which Chomsky drew his ideas and draw the limits of his theory. Chomsky’s innovation was an extension of the Cartesian rational heritage, which was the most important pillar of his theory of obstetrics. Descartes’ philosophy was therefore clearly influenced by Chomsky’s thought. To this end, our research dealt with the study of the influence of Descartes on Chomsky’s theory and its analysis of language, according to an epistemo- logy in which the mind is fully present in which we tried to answer the following question: How did Descartes put forward Chomsky’s analysis and analysis of the work of language and reason? As well as the analysis of language instinct under that comprehensive view.